Beating The Odds: Social Studies Education In Inner-City Detroit - Taylor, Julie Anne; Thomas-Brown, Karen (Teaching History: A Journal of Methods, 2011)
Despite the worsening financial crisis in the Detroit Public Schools, Cass Technical High School continues to be one of the highest achieving high schools in the state of Michigan. On social studies assessments, Cass students score significantly higher than the statewide average. While acknowledging that their courses are challenging, the students use words rarely associated with social studies classes: fun, interesting, and exciting. A unique teaching and learning environment has been created at the school by caring and motivated social studies educators who maintain high standards while using innovative methodologies. This study examines the social studies department at Cass Technical High School, offering the perspectives of both the students and the teachers. With over 2,000 students, Cass Technical High School in downtown Detroit faces significant social and economic challenges. Once a thriving metropolis, Detroit has been impacted profoundly by the decline of the American automobile industry. An estimated one third of the residents of Detroit now live below the poverty line, and Detroit has the lowest median household income of any city in the country.1 Forty one percent of the students at Cass are considered to be economically disadvantaged.2 Nevertheless, they consistently outperform other students on state achievement tests; in social studies, their scores are significantly higher than the statewide average. This study examines the reasons, cited by students and teachers, at the school, for the enduring success.